Bisophosphonates in the treatment of osteoporosis in women with breast cancer - Wolska, Joanna (Journal of Education, Health and Sport, 2019)
Abstract Osteoporosis is the most common skeletal disorder. It is characterized by a decrease in bone density, which results in a greater likelihood of hip, vertebral and long bone fractures. Women who are undergoing hormonal treatment for hormone-related breast cancer are particularly at risk for osteoporosis. Among women diagnosed with premenopausal breast cancer, therapeutic activities may result in secondary loss of ovarian function or include complete hormonal blockade. Long-term reduction of estrogen concentration adversely affects bone metabolism. It is recommended to assess the risk of bone fractures with densitometry in patients with hormone blockade effects. Calcium and vitamin D supplementation, moderate exercise is recommended. If bone mineral density is reduced, consideration should be given to initiating bisphosphonate therapy. Bisphosphonates inhibit bone resorption mediated by osteoclasts. The most important is the division into two classes: compounds containing no nitrogen (called simple bisphosphonates) and containing nitrogen. This division carries a significant difference in the strength of bone resorption inhibition and a different mechanism of action.